Pre-clinical anti-tumor activity of Bruton's Tyrosine Kinase inhibitor in Hodgkin's Lymphoma cellular and subcutaneous tumor model. Issue 8 (August 2019) - Muqbil, Irfana; Chaker, Mahmoud; Aboukameel, Amro; Mohammad, Ramzi M.; Azmi, Asfar S.; Ramchandren, Radhakrishanan
Abstract: Bruton's Tyrosine Kinase (BTK) is a member of the TEC family and plays a central role in B-cell signaling, activation, proliferation and differentiation. Here we evaluated the impact of BTK inhibitor Ibrutinib on a panel of HL models in vitro and in vivo. Ibrutinib suppressed viability and induced apoptosis in 4 HL cell lines in a dose and time dependent manner. Molecular analysis showed induction of both apoptotic and autophagy markers. Ibrutinib treatment resulted in suppression of BTK and other downstream targets including PI3K, mTOR and RICTOR. Ibrutinib given at 50 mg/kg p.o daily for three weeks caused statistically significant inhibition of HL cell line derived subcutaneous xenografts (p < 0.01) in ICR-SCID mice. Molecular analysis of residual tumor tissue revealed down-regulation of BTK; its related markers and autophagy markers. Our studies are the first showing in vitro and in vivo action of BTK inhibition in classical HL. A phase II study examining the activity of ibrutinib in relapsed or refractory HL is currently enrolling (NCT02824029 ).